KANDUNGAN IODIUM DALAM GARAM TAHUN 2003 DAN 2012 DI KABUPATEN BANYUMAS - Dardjito, Endo (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2013)
ABSTRACT   Endemic goitre is one of problems of nutrition in the Banyumas, especially the regions of mountains such as Districts, and tune the Baturaden, Pekuncen, Sumbang. Survey results conducted in 1980 found as much as 27% incidence of mumps has declined sharply, and when implemented in the 1996 survey and there is only as much as 3.5%, increased as much as 11,4 % survey in 2007. One of the efforts made to reduce the prevalence of goiter was popularized by beriodium salt. The purpose of this research is to know the content of iodium in salt in circulation in 2003 and 2012. Sample research is outstanding in the market salt in Banyumas randomly selected. Data collection was carried out in 2003 and 2012. To know the content of iodine in salt iodine test is done through and continued with the test titration. In general the content of iodium in salt dropped from 75.4% (2003 survey) into 48,7% (survey in 2012), most of the salt had circulated iodium trademarks (98.4% survey 2003) and 89,4% by 2012, survey), most (89.2%) of salt shaped smooth iodium circulating (as of 2003 survey) decreased to 56.3% (survey in 2012) and the majority (74.2%) both have outstanding salt trademarks (2003 survey) to decline increased to 83.1% (survey in 2012). The need for improved monitoring and surveillance by employing service related to salt beriodium circulating on the market to maintain quality/quality of salt (30 - 80 ppm), the need for strict sanctions by the rules that apply to producers of salt/seller of iodium salt  are not eligible (& lt; 30 ppm) by Department/Agency that has the authority, the Test simply through a solution of yodina test needs to be further enhanced and promoted Keywords: iodine content,  salt, titration test. Kesmasindo, Volume 6, (1) Januari 2013, Hal. 43-53